2020
DOI: 10.1002/hed.26365
|View full text |Cite
|
Sign up to set email alerts
|

Affective symptoms and swallow‐specific quality of life in total laryngectomy patients

Abstract: Background: The aim of this study is to determine the prevalence of clinically relevant affective symptoms and level of swallow-specific quality of life (QoL) in dysphagic patients with total laryngectomy (TL) and to explore the relationship between affective symptoms and swallow-specific QoL. Methods: Thirty-five TL patients completed the Hospital Anxiety and Depression Scale (HADS) and the MD Anderson Dysphagia Inventory (MDADI). Student's t test and linear regression were used. Results: Eight (23%) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…14 Small studies found those with depressive symptoms reported poorer swallowing-specific QOL outcomes. 15,16 A systematic review found symptoms of depression were common in patients with dysphagia of mixed aetiologies, observing associations with both swallowing impairment measures as well as self-report questionnaires, although few studies recruited both dysphagic and non-dysphagic participants. 17 A small difference in Hospital Anxiety and Depression Scale (HADS) scores for both depression and anxiety was noted in HNC survivors who aspirated on drinks compared to those who did not, 18 suggesting that swallowing impairment negatively impacted on mood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Small studies found those with depressive symptoms reported poorer swallowing-specific QOL outcomes. 15,16 A systematic review found symptoms of depression were common in patients with dysphagia of mixed aetiologies, observing associations with both swallowing impairment measures as well as self-report questionnaires, although few studies recruited both dysphagic and non-dysphagic participants. 17 A small difference in Hospital Anxiety and Depression Scale (HADS) scores for both depression and anxiety was noted in HNC survivors who aspirated on drinks compared to those who did not, 18 suggesting that swallowing impairment negatively impacted on mood.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively strong correlation between swallowing self‐report and QOL outcomes ( r = 0.69–0.83) was reported in the first year following radiotherapy, but the number recruited to the study was relatively small ( n = 167) 14 . Small studies found those with depressive symptoms reported poorer swallowing‐specific QOL outcomes 15,16 . A systematic review found symptoms of depression were common in patients with dysphagia of mixed aetiologies, observing associations with both swallowing impairment measures as well as self‐report questionnaires, although few studies recruited both dysphagic and non‐dysphagic participants 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Being able to swallow is the third major concern of patients diagnosed with laryngeal cancer in relation to treatment of the disease, only after the cure of cancer and the expectation of living as long as possible 9 . Swallowing disorders following total laryngectomy can lead the patient to eating alone or losing the pleasure to eat, which can lead to impairment in social function and a decrease in quality of life [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is understood that dysphagia can restrict an individual's relationship with their daily life, which allows us to assume that psychiatric disorders such as Common Mental Disorders (CMD) might emerge. The intensity and chronicity of CMD are related to developing diseases such as anxiety and depression [10][11][12][13][14] , which is why CMD screening is important in patients with swallowing complaints, especially in cases associated with head and neck cancer in which there is a markedly greater risk of psychological distress and worse quality of life 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation